Attitudes of pet owners in coastal Oaxaca, Mexico, towards pet ownership and access to care - Schulte, Rachael; Arcega Castillo, Guillermo; Wilkins, Melinda J. (Frontiers in Veterinary Science, 2025)
Free-roaming dogs pose risks to human, animal, and environmental health, through zoonotic disease transmission, contribution to parasite life cycles, and predation on vulnerable species. Sterilization campaigns are a common method to reduce free-roaming dog populations. A questionnaire was developed to assess the attitudes and practices of dog owners in coastal Oaxaca, Mexico, regarding pet ownership and access to veterinary care. The primary reasons for owning dogs were companionship and protection, and the most common barriers to care reported were cost and access. The professionalism, knowledge, and communication of veterinarians was rated highly, suggesting veterinarians are a trusted source of information and should play an important role in education efforts around zoonotic diseases and animal care, including population management. Short-term sterilization campaigns are effective at reducing free-roaming dog populations and have demonstrated benefits to local wildlife species through reducing predation. These campaigns, however, do not create sustainable change on their own; building local veterinary surgical capacity is an important need in rural Oaxaca.